Determination of Some Common Zoonotic Diseases Among Vulnerable Communities in an Africa Country - Umaru, Isaac John; Emmanuel, Okoli (Darul Yasin Al Sys, 2025)
This study investigated the determinants of zoonotic diseases in vulnerable communities in Africa with clear example of Ghana, focusing on the Ashanti and Northern regions. A cross-sectional study design was employed, using quantitative surveys and qualitative interviews to assess socio-demographic factors, knowledge, cultural beliefs, hygiene practices, and healthcare access among 846 households. The findings rsevealed differences in zoonotic disease dynamics between the regions. The Ashanti region exhibited higher awareness of zoonotic diseases (39%) compared to the Northern region (29%), while the Northern region showed a higher prevalence of risky practices such as bush meat consumption and free-roaming livestock. Both regions struggled with poor sanitation and limited healthcare access, with open defecation being more prevalent in the Northern Region (42%) than in the Ashanti Region (27%). Misconceptions about disease causation and reliance on traditional healers were also more pronounced in the Northern Region. The study highlights the need for multi-sectoral interventions, including targeted education, healthcare improvements, and culturally sensitive strategies, to mitigate the burden of zoonotic diseases in these communities, with regional differences informing targeted approaches. Ultimately, the study successfully identified key determinants of zoonotic diseases in the Ashanti and Northern regions, thereby achieving its aims and objectives.